AN ECOLOGICAL PARADIGM: After Communion Ecclesiology of Vatican II - Mularikkal, Jomon (Journal of Dharma, 2012)
The agrarian world kept their desire to plant their feet firmly on mother earth. There was a sense of rootedness and connectedness to the earth as a created reality.The importance of the earth is not only because it provides human needs, but also because “the earth carries the psychic structure as well as the physical form of every living being upon the planet.” Mountains and huge rocks balance the earth. But economic growth and technological advancements play a serious role in disturbing earth and soil. By the emergence of large earth movers and transportation facilities the face of the earth is fast changing. Ancient Church buildings and other institutions on the hilltops gave an impression that we are the caretakers of the Nature. But today instead of taking care of the earth, we empty the earth by selling the soil and constructing unbearable huge buildings. In this context the Church has a vital role to recapture the image as the “blessing to the nations” (Genesis 22:18). While the Catholic Church is celebrating the 50th year of the opening of Second Vatican Council, the communion ecclesiology of the Councul could shed light on our earth concerns providing a new ecological paradigm.